Concentration of antibodies against Porphyromonas gingivalis is increased before the onset of symptoms of rheumatoid arthritis. Issue 1 (December 2016) - Johansson, Linda; Sherina, Natalia; Kharlamova, Nastya; Potempa, Barbara; Larsson, Barbro; Israelsson, Lena; Potempa, Jan; Rantapää-Dahlqvist, Solbritt; Lundberg, Karin
Abstract Background The periodontal pathogenPorphyromonas gingivalis is hypothesized to be important in rheumatoid arthritis (RA) aetiology by inducing production of anti-citrullinated protein antibodies (ACPA). We have shown that ACPA precede RA onset by years, and that anti-P. gingivalis antibody levels are elevated in RA patients. The aim of this study was to investigate whether anti-P. gingivalis antibodies pre-date symptom onset and ACPA production. Methods A case–control study (251 cases, 198 controls) was performed within the Biobank of Northern Sweden. Cases had donated blood samples (n = 422) before the onset of RA symptoms by 5.2 (6.2) years (median (interquartile range)). Blood was also collected from 192 RA patients following diagnosis. Antibodies againstP. gingivalis virulence factor arginine gingipainB (RgpB), and a citrullinated peptide (CPP3) derived from theP. gingivalis peptidylarginine deiminase enzyme, were analysed by ELISA. Results Anti-RgpB IgG levels were significantly increased in pre-symptomatic individuals (mean ± SEM; 152.7 ± 14.8 AU/ml) and in RA patients (114.4 ± 16.9 AU/ml), compared with controls (p < 0.001). Anti-CPP3 antibodies were detected in 5 % of pre-symptomatic individuals and in 8 % of RA patients, with elevated levels in both subsets (4.33 ± 0.59 and 9.29 ± 1.81 AU/ml, respectively) compared with controls (p < 0.001). Anti-CPP3 antibodies followed the ACPA response, with increasing concentrations over time, whilst anti-RgpB antibodies were elevated and stable in the pre-symptomatic individuals with a trend towards lower levels after RA diagnosis. Conclusions Anti-P. gingivalis antibody concentrations were significantly increased in RA patients compared with controls, and were detectable years before onset of symptoms of RA, supporting an aetiological role forP. gingivalis in the development of RA.